Healthcare costs related to respiratory syncytial virus in paediatric intensive care units in the Netherlands: a nationwide prospective observational study (the BRICK study)Research in context - Emily W.E.M. Phijffer; Joanne G. Wildenbeest; Carole N.M. Brouwer; Matthijs de Hoog; Martin C.J. Kneyber; Sofie Maebe; Anneliese Nusmeier; Maaike A. Riedijk; Roelie M. Wösten-van Asperen; Job B.M. van Woensel; Louis J. Bont; Geert J.W. Frederix (Elsevier, 2024)
Summary: Background: The implementation of the approved respiratory syncytial virus (RSV) preventive interventions in immunisation programmes is advancing rapidly. Insight into healthcare costs of RSV-related paediatric intensive care unit (PICU) admissions is lacking, but of great importance to evaluate the impact of implementation. Therefore, this study aimed to determine the total annual RSV-related paediatric intensive care healthcare costs in the Netherlands. Methods: A nationwide prospective, observational, multicenter study was performed from September 2021 until June 2023. The total annual RSV-related healthcare costs on PICUs in the Netherlands were calculated using RSV-related costs (subgroup I) and consequential costs (subgroup II and III). Subgroup I comprised all PICU admitted infants ≤12 months of age with laboratory-confirmed RSV infection. Subgroup II and III consisted of postponed elective PICU admissions and refused acute PICU admissions due to RSV-related lack of PICU capacity. Findings: A total of 424 infants with RSV-related PICU admission were included. Median age at PICU admission was 46 days (IQR 25-89). The median length of PICU admission was 5 days (IQR 3-8). The total RSV-related PICU costs are € 3,826,386 in 2021-2022, and € 3,183,888 in 2022-2023. Potential costs averted by RSV preventive interventions is € 1.9 to € 2.6 million depending on season, and the duration of protection. Interpretation: RSV-related PICU admissions cost €3.1 to €3.8 million in the Netherlands during one season. The introduction of new RSV preventive interventions into the Dutch immunisation programme will generate significant cost-savings on PICUs and decreases the admission burden of PICUs. Funding: None.